2011
DOI: 10.3357/asem.2668.2010
|View full text |Cite
|
Sign up to set email alerts
|

Appendix A

Abstract: Results of the current study strongly suggest that intranasal scopolamine is efficacious for the treatment of motion sickness in susceptible individuals with no significant cognitive or sedative effects. Intranasal delivery offers a promising alternative for use in dynamic operational environments without cognitive detriment or increased side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…With incremental exposure, people also can develop context specific adaptations so that, for example, they can move between a rotating artificial gravity environment and a stationary environment without either sensory motor control or motion sickness problems (Graybiel and Knepton 1978a, b; Lackner and DiZio 2000a, b, 2006). Drugs such as promethazine and scopolamine provide protective benefit (Bar et al 2009; Davis et al 1993; Graybiel and Lackner 1987; Gordon et al 2001; Klocker et al 2001; Nachum et al 2001, 2006; Simmons et al 2010). These drugs are central nervous system depressants and induce drowsiness so that they are often used in combination with dexedrine and ephedrine, respectively.…”
Section: How Can Motion Sickness Be Avoided or Attenuated?mentioning
confidence: 99%
“…With incremental exposure, people also can develop context specific adaptations so that, for example, they can move between a rotating artificial gravity environment and a stationary environment without either sensory motor control or motion sickness problems (Graybiel and Knepton 1978a, b; Lackner and DiZio 2000a, b, 2006). Drugs such as promethazine and scopolamine provide protective benefit (Bar et al 2009; Davis et al 1993; Graybiel and Lackner 1987; Gordon et al 2001; Klocker et al 2001; Nachum et al 2001, 2006; Simmons et al 2010). These drugs are central nervous system depressants and induce drowsiness so that they are often used in combination with dexedrine and ephedrine, respectively.…”
Section: How Can Motion Sickness Be Avoided or Attenuated?mentioning
confidence: 99%
“…Furthermore scopolamine nasal spray [77,78] was found to be an effective and safe treatment in motion sickness, with a fast onset within 30 min after administration.…”
Section: Prevention and Treatment Of Motion Sicknessmentioning
confidence: 99%
“…The benefits of IN administration include greater acceptance by patients, particularly children, and the access that the IN route provides to the CNS, thus avoiding first pass clearance by the liver and potential toxicity to non-target organs. Recent successes include use of IN-administered midazolam for the treatment of status epilepticus in children and young adults (McMullan et al, 2010); IN scopolamine for motion sickness (Simmons et al, 2010), and IN insulin has been shown to improve cognition in early Alzheimer’s disease (Benedict et al, 2004). …”
Section: Introductionmentioning
confidence: 99%